Vogel's Medium N salts: avoiding the need for ammonium nitrate - Robert L. Metzenberg (Fungal Genetics Reports, 2003)
Vogel's Medium N salts (Vogel, 1956 Microbiol. Genet. Bull. 13:42-43), supplemented with a carbon source, is widely used for the cultivation of Neurospora and many other fungi. The standard recipe includes ammonium nitrate.